IMPLEMENTASI NILAI-NILAI RELIGIUS DALAM MENGUATKAN CIVIC RESPONSIBILTY SISWA SMP MUHAMMADIYAH 2 PONTIANAK - Feriyadi, Feriyadi; Asriati, Nuraini; Purnama, Shilmy; Sulistyarini, Sulistyarini; Utami, Tri (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
This study aims to describe the implementation of religious values in strengthening civic responsibility among students at SMP Muhammadiyah 2 Pontianak, focusing on religious program planning, religious activity implementation, evaluation, and supporting and inhibiting factors. This study uses a descriptive qualitative approach with data collection techniques in the form of observation, interviews, and documentation of the principal, civics teachers, Islamic Education teachers, homeroom teachers, and students from each grade level. The results show that religious values are applied through the habit of worship such as the dhuha prayer, tadarus, congregational zuhur prayer, kultum, clean Friday, and the habit of religious attitudes through the example set by teachers. The implementation of these religious values has a significant impact on students' civic responsibility, as reflected in increased discipline, concern for the environment, ability to work together, courage to express opinions, and moral awareness among students. The main supporting factors for the successful implementation of the program are teacher role models, a religious school culture, and the integration of religious values in civic education. The obstacles encountered were the influence of the environment and social media, differences in family backgrounds, and limited facilities. This study concluded that the internalization of religious values is an effective strategy in strengthening students' civic responsibility when applied consistently, comprehensively, and sustainably. ABSTRAK Penelitian ini bertujuan untuk mendeskripsikan implementasi nilai-nilai religius dalam menguatkan civic responsibility siswa di SMP Muhammadiyah 2 Pontianak, dengan fokus pada perencanaan program religius, pelaksanaan kegiatan keagamaan, evaluasi, serta faktor pendukung dan penghambat. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan teknik pengumpulan data berupa observasi, wawancara, dan dokumentasi terhadap kepala sekolah, guru PKn, guru Pendidikan Agama Islam, wali kelas, serta siswa dari setiap jenjang. Hasil penelitian menunjukkan bahwa nilai-nilai religius diterapkan melalui pembiasaan ibadah seperti shalat dhuha, tadarus, shalat zuhur berjamaah, kultum, Jumat bersih, serta pembiasaan sikap religius melalui keteladanan guru. Implementasi nilai religius tersebut berdampak signifikan terhadap civic responsibility siswa, tercermin dari meningkatnya kedisiplinan, kepedulian terhadap lingkungan, kemampuan bekerja sama, keberanian menyampaikan pendapat, serta kesadaran moral siswa. Faktor pendukung utama keberhasilan implementasi program adalah keteladanan guru, budaya sekolah religius, dan integrasi nilai religius dalam pembelajaran PKn. Hambatan yang ditemukan yaitu pengaruh lingkungan dan media sosial, perbedaan latar belakang keluarga, serta keterbatasan fasilitas. Penelitian ini menyimpulkan bahwa internalisasi nilai-nilai religius merupakan strategi efektif dalam memperkuat civic responsibility siswa apabila diterapkan secara konsisten, menyeluruh, dan berkelanjutan.